The Influence of Instagram Advertising and Food Quality Toward Revisit Intention at Kungfu Kebab Serpong (A Case Study of Kungfu Kebab- Serpong) - gracia puteri, eunike; nova putra, aditya; m. nawangwulan, irma; nurfitriana, siti (IULI Publisher, 2024)
The aim of this research is to observe the impact of Instagram Advertising, and Food Quality to Revisit Intention at Kungfu Kebab Serpong. This research was conducted in Kungfu Kebab Serpong. It is a restaurant in Serpong which sells premium Turkish kebab. The design of this research is using descriptive and quantitative research which shows the correlation between variables. The technique of collecting data was done using questionnaire to 113 respondents. The technique of analysing data was done using structural equation modelling (SEM) by SPSS statistics 26 and AMOS software version 24. The result of this research shows that the Instagram Advertising shown very weak influence with 0.373 to Revisit Intention. The Food Quality has a positive and significant impact of 0.829 to Revisit Intention. It means that the correlation between Instagram Advertising slightly influence but not significant toward Revisit Intention. However, the correlation between Food Quality shown significant or strong influence to Revisit Intention at Kungfu Kebab Serpong. Keywords: Instagram Advertising, Food Quality, Revisit Intention